Analysis of Economic Improvement to Reduce Poverty in 2016-2020 - Dewi Fatmasari; Dikdik Harjadi; Abas Hidayat (Khazanah Sosial, 2022)
Being helpless, unwelcome, and lacking a sense of freedom are the three characteristics of poverty. A country that is said to be prosperous can be seen from high economic growth. Economic growth influences reducing the problem of poverty. The lower the level of poverty will cause various kinds of socio-economic problems in a country. This study aims to find the direct and indirect effect of the independent variables, namely the effect of the General Allocation Fund (DAU), Regional Original Income (PAD), and Special Allocation Fund (DAK) on Poverty through Economic Growth. The research is a quantitative study using the regression analysis method by combining cross-section and time series data using Eviews 9.0 Software. This study took the object of research in 29 regencies in West Java Province for the period 2016 - 2020. Panel data source from the provincial annual report, Director General of Balance, Ministry of Finance, West Java BPS. The results of the study show that general allocation funds have a significant effect on economic growth. Special allocation funds have a significant effect on economic growth. However, local revenue does not have a significant effect on economic growth. This study contributes that the economic improvement plays an important role in reducing poverty.